The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1103/physrevb.59.2773
|View full text |Cite
|
Sign up to set email alerts
|

Electron paramagnetic resonance and photoluminescence study of Er-impurity complexes in Si

Abstract: Electron paramagnetic resonance ͑EPR͒ and photoluminescence ͑PL͒ spectroscopy have been used to examine the structure and optical properties of erbium-impurity complexes formed in float-zone Si by multipleenergy implants at 77 K of Er together with either O or F. After implantation a 2-m-thick amorphous layer was formed containing an almost uniform concentration of Er (10 19 /cm 3 )and O (3ϫ10 19 /cm 3 or 10 20 /cm 3 ) or F (10 20 /cm 3 ). Samples were annealed in nitrogen at 450°C for 30 min ͑treatment A͒, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 28 publications
2
49
1
Order By: Relevance
“…In the case of line L 1 1 , the average g av value for the lowest level of the ground state is 6.1 AE 0.5, slightly smaller than the 6.8 value characteristic for pure À 6 and similar to values found for Er in different host materials [16], [67]- [70]. Therefore the lowest level of Er-1 ground state is likely to be of the À 6 character.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In the case of line L 1 1 , the average g av value for the lowest level of the ground state is 6.1 AE 0.5, slightly smaller than the 6.8 value characteristic for pure À 6 and similar to values found for Er in different host materials [16], [67]- [70]. Therefore the lowest level of Er-1 ground state is likely to be of the À 6 character.…”
mentioning
confidence: 55%
“…Extended X-ray absorption fine structure spectroscopy [13] revealed the presence of six oxygen atoms in the immediate surrounding of the local site of an Er atom in Czochralski (Cz) Cz-Si:Er [13], [14] and 12 Si atoms in float-zoned (Fz) Fz-Si:Er. These findings were confirmed by Rutherford back-scattering [15] and electron paramagnetic resonance studies [16]. Channeling experiments by Wahl et al [17] identified the formation of an Er-related cubic center at a tetrahedral interstitial site ðT i Þ as the main center generated in c-Si by Er implantation.…”
Section: ) Incorporationmentioning
confidence: 78%
“…[15] and based upon the similarities of the g values and point symmetry of centre OEr-3 to centre OEr-1, these two centres are believed to have very similar structures. However, the exact arrangement of these defect complexes within the Si lattice was unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It can be regarded as proven that O forms complexes with Er which directly modify the structural, electrical and optical properties of Er [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, there is also strong evidence that, possibly apart from ErO complex formation, additional mechanisms exist how O enhances the Er luminescence yield [6,7].…”
Section: Introductionmentioning
confidence: 99%